Linkage Between Product Line Strategy and Competitive Advantage: Does Environmental Dynamism Matter? - Abubakar , Ismaila; Usman, Sani Audu; Nuhu, Abdulrazak (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2022)
Changes in the operating environment normally force many firms to reconsider and adopt new strategies in search of new techniques and innovative management philosophies that can improve their competitiveness. This study is aimed at investigating the link between product line strategy and competitive advantage taking into consideration frequency and intensity of change in the operating environment, and enhancing the literature on strategic management and competitive advantage. The study involved a questionnaire-based survey of managers from a variety of manufacturing firms in Nigeria. A total of 215 responses were received and subjected to multiple regression analyses. Findings of the study revealed that product line strategy, which involves vertical and horizontal line extension line modernization and line pruning strategies constructs, has a significant effect on the firm’s competitive advantage. Further, that the relationship between product line strategy and firm competitive advantage was influenced by the environmental dynamism construct including changes in industry, competition and consumer. This study can help managers to understand the role of changes in environmental factors when formulating strategies concerning their product line. We, therefore, concluded that managers and other decision-makers can make informed decisions on the product line by paying attention to the firm’s external environment.